Pathogenesis and Management of Pruritus in PBC and PSC - Kremer, Andreas; Namer, Barbara; Bolier, Ruth; Fischer, Michael; Elferink, Ronald P. Oude; Beuers, Ulrich (Digestive Diseases, 2015)
Pruritus is a preeminent symptom in patients with chronic cholestatic liver disorders such as primary biliary cirrhosis and primary sclerosing cholangitis. More than two-thirds of these patients experience itching during the course of their disease. This symptom is also frequently observed in patients with other causes of cholestasis such as cholangiocarcinoma, inherited forms of cholestasis and intrahepatic cholestasis of pregnancy, but may accompany almost any other liver disease. The pathogenesis of pruritus of cholestasis remains largely elusive. Increased concentrations of bile salts, histamine, serotonin, progesterone metabolites and endogenous opioids have been controversially discussed as potential pruritogens. However, for these molecules, neither a correlation with itch intensity nor a causative link could be established. The G protein-coupled receptor for bile salts, TGR5, has been shown to be expressed in dorsal root ganglia and give rise to itch in rodents, albeit upon stimuli with suprapathological concentrations of bile salts. The potent neuronal activator lysophosphatidic acid (LPA) and its forming enzyme, autotaxin (ATX), could be identified in the serum of patients with cholestatic pruritus. ATX activity correlated with itch severity and effectiveness of several anti-pruritic therapeutic interventions in cholestatic patients. Thus, the ATX-LPA-axis may represent a key element in the pathogenesis of this agonizing symptom. Treatment options for pruritus of cholestasis remain limited to a few evidence-based and several experimental medical and interventional therapies. The current guideline-based recommendations include the anion exchange resins colestyramine, the pregnane X receptor-agonist and enzyme inducer rifampicin, the ?-opioid antagonist naltrexone, and the selective serotonin reuptake inhibitors sertraline. Still, a considerable part of patients is unresponsive to these drugs and requires experimental approaches including phototherapy, plasmapheresis, albumin dialysis or nasobiliary drainage. This review outlines the current knowledge on pathogenesis of cholestatic pruritus and summarizes evidence-based and experimental therapeutic interventions for cholestatic patients with itch.
EVALuna2:1849